Prognostic value of remnant-like particle cholesterol in ischemic heart failure patients following percutaneous coronary intervention - Xin Huang; Tienan Sun; Biyang Zhang; Meishi Ma; Zheng Chen; Zehao Zhao; Shutong Dong; Yujie Zhou (Annals of Medicine)
Background The relationship between remnant-like particle cholesterol (RLP-C) and cardiovascular disease risk and prognosis has been established, but its effect on the prognosis of ischemic heart failure (IHF) patients undergoing percutaneous coronary intervention (PCI) remains uncertain.Method In this study, 2036 patients with IHF who underwent PCI were included. Patients were categorized into tertiles based on their RLP-C levels. The primary outcome was major adverse cardiovascular events (MACE). Kaplan-Meier survival analysis was used to assess the incidence of MACE and other outcomes. Multivariate Cox regression models were employed to investigate the correlation between RLP-C and the studied outcomes. The nonlinear relationship between RLP-C and MACE was examined through the restricted cubic spline (RCS). Subgroup analyses were performed and interactions were assessed.Result The study results showed a clear association between higher RLP-C levels and an increased incidence of MACE in the participants. This association was validated by Kaplan-Meier analyses. The multivariate Cox regression demonstrated RLP-C was an independent risk factor for MACE, whether assessed as a continuous variable[hazard ratio (HR), 95% confidence interval (CI): 1.50, 1.15-1.98, p = 0.003] or categorized into tertiles[HR, 95% CI: 2.57, 2.03-3.26, p < 0.001, tertile 3 vs tertile 1]. A nonlinear relationship between RLP-C and MACE was observed, indicating that the risk of MACE increased with higher RLP-C levels(Nonlinear p < 0.001). This association remained consistent across various subgroups, as no significant interactions were found.Conclusion There was an independent and positive correlation between RLP-C and MACE in patients with IHF who underwent PCI.